Estimation of Breeding Values and Genetic Variances at First Exon-region of IGF1 Gene and its Association of Growth Traits in Awassi Sheep which are Breeding in Iraq - Zaid Mohammed Mahdi Al-Azzawi; Bashar Adham Ahmed; O.H. Shihab; Ziyad T. Aldoori (The Indian Veterinary Journal, 2025)
The study aimed to determine the breeding values and genetic. Variation based on the information of the genetic polymorphism of the first exon region of IGF1 gene using by RFLP and its relationship to growth traits (birth weight, weaning weight, and average daily gain ). The study was conducted at the Ruminant Research Station of the General Authority for Agricultural Research / Ministry of Agriculture a sample of 55 Awassi Turkey ewes in the animal breeding station in Baghdad and the Center for Biotechnology / University of Al-Nahrain. The breeding value (BV) of genotype BB was higher (4.04) compared with AA and AB (3.72 and 3.88) for the birth weight (BWT) respectively, while BV was higher for AA genotype in weaning weight (WWT) and average daily gain (ADG) traits (20.47 and 16.34), respectively. It is found that the value of dominance variance (VD) within the genetic variation is high as compared with the additive variance (VA) in WWT and ADG it reached 0.037 and 0.018 which indicates the effect of the dominance interaction on thesis traits. The average of the allele effect and the effect of substitution of alleles were a favor for the allele A compared to mutant allele (B), which gives evidence about the direction for the selection of the dominant allele, as the frequency of allele A was more distributed (0.70) in the studied sample, so it is necessary to maintain the frequency of this allele and increase its frequency with the help of selection with genetic markers.